Decoding sTREM2: its impact on Alzheimer’s disease – a comprehensive review of mechanisms and implications - Lin, Cui; Kong, Yu; Chen, Qian; Zeng, Jixiang; Pan, Xiaojin; Miao, Jifei (Frontiers in Aging Neuroscience, 2024)
Soluble Triggering Receptor Expressed on Myeloid Cells 2 (sTREM2) plays a crucial role in the pathogenesis of Alzheimer's disease (AD). This review comprehensively examines sTREM2's involvement in AD, focusing on its regulatory functions in microglial responses, neuroinflammation, and interactions with key pathological processes. We discuss the dynamic changes in sTREM2 levels in cerebrospinal fluid and plasma throughout AD progression, highlighting its potential as a therapeutic target. Furthermore, we explore the impact of genetic variants on sTREM2 expression and its interplay with other AD risk genes. The evidence presented in this review suggests that modulating sTREM2 activity could influence AD trajectory, making it a promising avenue for future research and drug development. By providing a holistic understanding of sTREM2's multifaceted role in AD, this review aims to guide future studies and inspire novel therapeutic strategies.